Students' Perspectives on the Academic Burden of College - Aisyatun Anggina; Hikmah Dalila Tanjung; Juna Marta Sari Panggabean; Sandi Pradana (SocioSphere: Interdisciplinary Journal of Social Sciences and Humanities, 2025)
High academic burden is often the main trigger of stress among college students, which has a negative impact on their mental health, motivation to learn, and sleep quality. This study aims to examine the academic burden, influences, and strategies experienced by college students. The method used is a qualitative descriptive approach. Data were collected through in-depth interviews and literature studies from various relevant sources. The results of the analysis show that students who face excessive academic burden tend to experience significant stress, which can interfere with their psychological well-being and academic performance. Social support, especially from family and friends, has been shown to be more effective in helping students manage academic tasks. Therefore, it is important for educational institutions to pay attention to the academic burden given and provide adequate support services to improve students' well-being and academic success.